Hubungan Kehamilan Remaja dengan Kecemasan Persiapan Persalinan pada Ibu Hamil Trimester III di Puskesmas Amurang Timur - Paoki, Grace; Widia Shofa Ilmiah (Pusat Riset dan Inovasi Nasional, 2025)
Adolescent pregnancy increases the risk of psychological vulnerability, particularly during the labor process. Mental unpreparedness, lack of experience, and limited social support contribute to the heightened anxiety commonly experienced by adolescents approaching childbirth. This study aims to identify the relationship between adolescent age and the level of labor preparation anxiety among third-trimester pregnant women at UPTD Amurang Timur Public Health Center. A correlational quantitative design with a cross-sectional approach was employed. A total of 36 pregnant adolescents aged 14–19 years participated in this study. The instruments used included a demographic characteristics questionnaire and an anxiety assessment scale. Data were analyzed using Kendall’s Tau_b test. The results showed that 52.8% of respondents experienced severe anxiety. A significant negative correlation was found between age and anxiety levels (r = -0.516; p = 0.001), indicating that younger age was associated with higher anxiety levels. These findings highlight the urgent need for comprehensive antenatal interventions for pregnant adolescents, addressing both psychological and social dimensions.